6(-5n+1)+5n=-2n-40

Simple and best practice solution for 6(-5n+1)+5n=-2n-40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(-5n+1)+5n=-2n-40 equation:


Simplifying
6(-5n + 1) + 5n = -2n + -40

Reorder the terms:
6(1 + -5n) + 5n = -2n + -40
(1 * 6 + -5n * 6) + 5n = -2n + -40
(6 + -30n) + 5n = -2n + -40

Combine like terms: -30n + 5n = -25n
6 + -25n = -2n + -40

Reorder the terms:
6 + -25n = -40 + -2n

Solving
6 + -25n = -40 + -2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '2n' to each side of the equation.
6 + -25n + 2n = -40 + -2n + 2n

Combine like terms: -25n + 2n = -23n
6 + -23n = -40 + -2n + 2n

Combine like terms: -2n + 2n = 0
6 + -23n = -40 + 0
6 + -23n = -40

Add '-6' to each side of the equation.
6 + -6 + -23n = -40 + -6

Combine like terms: 6 + -6 = 0
0 + -23n = -40 + -6
-23n = -40 + -6

Combine like terms: -40 + -6 = -46
-23n = -46

Divide each side by '-23'.
n = 2

Simplifying
n = 2

See similar equations:

| 2x-(-2+x)=3 | | 10x+4x^2=66 | | 7/8p-r | | -(-5x+4)= | | -3x-5y=4 | | -y-15y-4y+13y+2y=20 | | -1(1-4x)=-22+x | | k^2+6+5k=0 | | 96-n=-23 | | 7q=9(q+4) | | 6-4x=-9x+8 | | 12+(-3)+(-1)= | | H=120t-16t^2 | | 1/4x-37.25=52.50 | | 8(-27)-11= | | y-8x=12 | | 2m-7=8+2m | | 2800=460+65m | | 2^20/2^3 | | 4=k/6 | | 4g-2g-g=10 | | -(1-4x)=22+x | | 2y-6x-12=0 | | 5/7x=40.5 | | 3m+-19=14 | | (y^2/3)^-9 | | 3m-19=24 | | 8*n=80 | | 6y+2x-y-x= | | .2/10 | | 3x-4x+2x+1-3= | | 9x^2+30x+1=0 |

Equations solver categories